Association between the History of Fall and the Fear of Falling on stair descent and gait transition spatio-temporal parameters and lower limb kinetics and kinematics in older adults: an observational study - Teles, Ivone da Silva (2023)
It has been estimated that 20% of the falls in older adults occur on stairs, mostly during stair descent during gait transition. Although History of Fall and Fear of Falling are related to a higher risk of falling in older adults, their association with biomechanical changes in this functional task has yet to be established. To evaluate the association between History of Fall and Fear of Falling on spatio-temporal, lower limb kinetic and kinematic parameters in older adults during stair descent and gait transition. Sixty older adults (>60 years) were evaluated through an optoelectrical motion capture system and two force plates during stair descent and gait transition. For the analysis it was used the mean value of the task velocity and time, single and double-support time, peak downwards center of mass velocity, hip, knee and ankle position, range of motion and power, foot clearance and foot placement, assessed using a multivariate analysis of variance. FOF exhibited longer task (p=0.009), double-support (p=0,047) and single-support (p=0,009) times and reduced peak downwards CoM velocity (p=0,043). In the stair cycle, FOF exhibited increased ankle power at heel-strike (p=0.026). In the gait cycle, HOF exhibited reduced initiating ankle angle at toe-off (p=0,015), increased initiating hip power at heel-strike (p=0,024) and contralateral ankle power at toe-off (p=0,029). FOF presented reduced initiating ankle angle at heel-strike (p=0.041) and toe-off (p=0.026) and reduced contralateral ankle angle at toe-off (p=0.022). Conclusion: In older adults, History of Fall and Fear of Falling are associated with changes in biomechanical parameters during stair descent and gait transition, consistent with the use of more conservative strategies to avoid falling.